Inflammation‐induced cholestasis in cancer cachexia. Issue 1 (22nd December 2020) - Thibaut, Morgane M.; Sboarina, Martina; Roumain, Martin; Pötgens, Sarah A.; Neyrinck, Audrey M.; Destrée, Florence; Gillard, Justine; Leclercq, Isabelle A.; Dachy, Guillaume; Demoulin, Jean‐Baptiste; Tailleux, Anne; Lestavel, Sophie; et al.
Abstract: Background: Cancer cachexia is a debilitating metabolic syndrome contributing to cancer death. Organs other than the muscle may contribute to the pathogenesis of cancer cachexia. This work explores new mechanisms underlying hepatic alterations in cancer cachexia. Methods: We used transcriptomics to reveal the hepatic gene expression profile in the colon carcinoma 26 cachectic mouse model. We performed bile acid, tissue mRNA, histological, biochemical, and western blot analyses. Two interventional studies were performed using a neutralizing interleukin 6 antibody and a bile acid sequestrant, cholestyramine. Our findings were evaluated in a cohort of 94 colorectal cancer patients with or without cachexia (43/51). Results: In colon carcinoma 26 cachectic mice, we discovered alterations in five inflammatory pathways as well as in other pathways, including bile acid metabolism, fatty acid metabolism, and xenobiotic metabolism (normalized enrichment scores of −1.97, −2.16, and −1.34, respectively; all P adj < 0.05). The hepatobiliary transport system was deeply impaired in cachectic mice, leading to increased systemic and hepatic bile acid levels (+1512 ± 511.6 pmol/mg, P = 0.01) and increased hepatic inflammatory cytokines and neutrophil recruitment to the liver of cachectic mice (+43.36 ± 16.01 neutrophils per square millimetre, P = 0.001). Adaptive mechanisms were set up to counteract this bile acid accumulation by repressing bile acid synthesis and by enhancing alternative routes of basolateral bile acid efflux. Targeting bile acids using cholestyramine reduced hepatic inflammation, without affecting the hepatobiliary transporters (e.g. tumour necrosis factor α signalling via NFκB and inflammatory response pathways, normalized enrichment scores of −1.44 and −1.36, all P adj < 0.05). Reducing interleukin 6 levels counteracted the change in expression of genes involved in the hepatobiliary transport, bile acid synthesis, and inflammation. Serum bile acid levels were increased in cachectic vs. non‐cachectic cancer patients (e.g. total bile acids, +5.409 ± 1.834 μM, P = 0.026) and were strongly correlated to systemic inflammation (taurochenodeoxycholic acid and C‐reactive protein: ρ = 0.36, P adj = 0.017). Conclusions: We show alterations in bile acid metabolism and hepatobiliary secretion in cancer cachexia. In this context, we demonstrate the contribution of systemic inflammation to the impairment of the hepatobiliary transport system and the role played by bile acids in the hepatic inflammation. This work paves the way to a better understanding of the role of the liver in cancer cachexia.